Prolanis Terhadap Tingkat Penurunan Tekanan Darah dan Diabetes Mellitus di Bungursari, Tasikmalaya - Eneng Daryanti; Rikky Gita H; Lina Marlina; Meti Sulastri (LPPM Universitas Muhammadiyah Tasikmalaya, 2020)
The government through BPJS Health has launched a chronic disease management program (PROLANIS) aimed at patients with hypertension cases to overcome the patient's hypertension condition. Activities in PROLANIS include medical or educational consultation activities, home visits, reminders, club activities, in fact there are still many people especially families who do not know about PROLANIS, so that many community members or families who have hypertension do not routinely control health facilities. The purpose of this activity is to run a chronic disease management program (prolanis) to reduce blood pressure and diabetes mellitus. The method used is lectures, discussions, home visits. Material or types of activities provided include health education about PROLANIS, hypertension and diabetes mellitus, attending elderly gymnastics, health consultations, checking blood pressure and blood sugar levels, and visiting home activities of PROLANIS members. Media used in the form of power points, blood pressure meters, blood sugar check devices, stethoscopes. The results of the assessment of this activity indicate the effectiveness of prolanis activities can affect the state of the patient, both blood pressure or physical activity. This is because there are activities that can improve patient understanding of the importance of managing hypertension and diabetes mellitus. Management of hypertension and diabetes mellitus is obtained through educational activities towards patients and reminders.